Bibliography on Winter Construction, 1967-1971 - Kaplar,Chester W.; Metrish,Robert M. (1974)
The bibliography covers world literature published during 1967-1971 on the subject of construction during cold weather. The contents are drawn mainly from the continuing current literature search performed by the Science and Technology Division of the Library of Congress for the U.S. Army Cold Regions Research and Engineering Laboratory. The contents include 746 items grouped into 17 categories, plus an author index. This bibliography is an addendum to the revised edition of USA CRREL Special Report 83, A Bibliography on Winter Construction, 1940-1967, published in 1968. (Author) See also AD-675 415.